البنيان القانوني للسفتجة الالكترونية على ضوء قانون التوقيع الألكتروني والمعاملات الالكترونية العراقي: دراسة مقارنة - مصطفى, سميرة عبد الله; فيض الله, حسين توفيق (Journal of Legal Sciences, 2019)
This paper  sheds  some light on the solutions provided for by the Iraqi legislator regarding securities under the provisions of the Law, No. 78 of 2013 (Law of electronic signature and electronic transactions). Secondly, it explores the legal nature of electronic promissory note and to what extent it can be used instead of the classical promissory note as its continuity as a means of the fulfillment of debts and credits specifically for paying  external  debts, and as a means of  competing with other instrument of electronic pay back of debts. Thirdly, it also clarifies whether this electronic promissory note can be an alternative for electronic signature and acceptance of a promissory note. Further, it explains whether the Iraqi legislator has successfully tackled the issue? Finally, it comes up with certain suggestions in this regard in order to insure finding a successful legal solution for the issue in question.